(untitled) (Global Journal of Science Frontier Research, 2023)
The possibility of experiencing things that may not be attainable in real life such as going to Mars swimming with dolphins or performing with the Rolling Stones can be realized through the application of Virtual Reality VR By utilizing computer graphics and Human-Computer Interaction HCI we can create a virtual environment that enables us to interact with almost any conceivable scenario In short VR technology enables us to see and experience anything through the power of computer-generated imagery Methods Findings The development of Virtual Reality VR Technology has introduced a new level of creativity Essentially VR technology involves using advanced technology to create the illusion of being present in an environment that is not physically present This is achieved by providing information to the senses such as sight and sound that tricks our brains into believing we are experiencing something virtual The illusion is often augmented by the presence of interactivity where the virtual world responds to our presence in some way However generating such virtual worlds requires advanced computer hardware and software as well as specialized peripheral devices that perform VRspecific functions While VR technology presents many advantages and applications there are also some challenges in fields such as criminology physical trauma and emotional relationships In this article we aim to present all the advantages and applications of VR technology while also categorizing and addressing open and solved issues in domains such as security social dilemmas and ethical dilemmas Application We have conducted a survey and consolidated the results in one place to assist future researchers in addressing other challenges in the field Consequently future VR researchers need not search multiple sources for solutions to related problems as they can find them in our study if they have been previously solved